The Bronze-Iron Age transition in Achaea, western Greece: continuity and change from the 12th to the 8th century BC - Marini, C (2018)
Achaea in the Northwest Peloponnese presents unique opportunities for the study of the Late Bronze-Iron Age transition in Western Greece. During the 12th century BC, its archaeological record suggests the existence of a thriving network of sites, with a high concentration in Western Achaea, whose elites propagated their warlike ethos in the funerary record and were able to nurture and sustain interregional and overseas contacts long after the demise of the palatial economies. The beginning of the Iron Age saw the disappearance of the conditions that prompted these developments, and brought drastic changes to burial customs and settlement patterns, with the shift of the regional centre of gravity towards Northeast Achaea. By the 8th century new political economies and social dynamics are manifested in the growth of local cult-sites. The present study explores these issues through the examination of the published settlement, funerary, and ceramic evidence. It also considers Achaea’s position in the wider context of Western Greece, through the lasting interactions visible in the ceramic production. Moreover, it addresses the character of the Achaean engagement in the communication networks towards the West, and peninsular Italy in particular, as these contacts were manipulated by the post-palatial elites and re-surfaced in a completely different framework in the late 8th century, with the Achaean involvement in the colonisation movement. The study of Achaea thus offers a regional perspective into the diverse socio-political and cultural transformations that occurred in the Aegean between the 12th and the 8th centuries BC. By elucidating aspects of continuity and change across this crucial transitional period it is possible to observe a regional shift from local chiefdoms with warlike ruling ideology communicated in the mortuary record, to communities structuring their identities in the sphere of communal cults.